2008
DOI: 10.1007/s11581-008-0304-2
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic disinfection of water with Ag–TiO2 nanocrystalline composite

Abstract: A method of solution impregnation and calcination has been demonstrated for synthesizing nanoparticles of Ag-TiO 2 composite photocatalysts for use in the disinfection of water. Only a small proportion of the TiO 2 surface is covered by nano-islands of Ag corresponding to a loading of 4 wt.% of Ag; thus, most of the TiO 2 surface is available for photocatalytic function. Although the primary particles of both Ag and TiO 2 are in the 10-to 20-nm range, microscopic studies indicate that the primary particles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 27 publications
1
17
0
2
Order By: Relevance
“…However, Ag/TiO 2 shows great promise as a photocatalytic material because of its photoreactivity and visible light response (Li et al . 2008) and are found to be significantly more photocatalytically and antimicrobially active than a titania coating (Kumar and Raza 2009). Zhang and Chen (2009) showed that by doping TiO 2 with metallic form of nanosilver, the bactericidal activity increased because of its unique structural feature of nanosilver dispersed on the TiO 2 surface and indicated that TiO 2 serve as a solid antiaggregation support to maintain the dispersion of nanosilver, which could also contribute to the antibacterial performance.…”
Section: Resultsmentioning
confidence: 99%
“…However, Ag/TiO 2 shows great promise as a photocatalytic material because of its photoreactivity and visible light response (Li et al . 2008) and are found to be significantly more photocatalytically and antimicrobially active than a titania coating (Kumar and Raza 2009). Zhang and Chen (2009) showed that by doping TiO 2 with metallic form of nanosilver, the bactericidal activity increased because of its unique structural feature of nanosilver dispersed on the TiO 2 surface and indicated that TiO 2 serve as a solid antiaggregation support to maintain the dispersion of nanosilver, which could also contribute to the antibacterial performance.…”
Section: Resultsmentioning
confidence: 99%
“…The images at higher magnification (Fig. 2f, i, l) indicate that the particles are roughly agglomerated, which could be attributed to the high surface energy of nanoparticles (Kumar and Raza 2009;Vamathevan et al 2002;Zhang et al 2003;Cao et al 2017).…”
Section: Resultsmentioning
confidence: 94%
“…This is because the internal convection of the aqueous segments enhanced the mass transfer arising from the segmented flow, which was beneficial to increase the growth rate of the biofilms. In addition, the oxygen input in the air segments was beneficial to increase the growth rate of biofilms [ 21 ]. Thus, fluid flow regimes have a significant impact on the structures and development of biofilms.…”
Section: Resultsmentioning
confidence: 99%